Improved Random Forest (RF) classifier for imbalanced classification of lung nodules - Paing, May Phu; Choomchuay, Somsak (My University, 2018)
Computer-aided detection (CAD) for lung cancer acts a dynamic research in biomedical engineering. These CADs generally occur imbalanced data classification because there are a large number of false lesions which are non-nodules (majority class), compared to the actual nodules (minority class). This paper proposes an improved random forest (RF) classifier to solve the learning bias problem of the imbalanced classification. The proposed RF applies sampling and three feature selection schemes namely Relief, Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) to improve the classification performance.
Keywords: genetic algorithm; imbalanced classification; partical swarm optimization; random forest; relieff